Synergistic effect of CD47 blockade in combination with cordycepin treatment against cancer - Feng, Chen; Chen, Rongzhang; Fang, Weiwei; Gao, Xinran; Ying, Hanjie; Zheng, Xiao; Chen, Lujun; Jiang, Jingting (Frontiers in Pharmacology, 2023)
Cordycepin was wildly considered as a direct tumor-suppressive drug, however, and as of now few studies have been presented to investigate the effect of cordycepin therapy to the tumor microenvironment (TME). In our study, we demonstrated that cordycepin would decrease the function of M1-like macrophage in TME, and also contribute to macrophage polarization (M2-macrophage). Herein, we tried to establish a combined therapeutic strategy of cordycepin and anti-CD47 antibody. Using single cell RNA sequencing, we improved that the combined treatment would significantly increase the effect of cordycepin, which would reactivate macrophages and reverse macrophage polarization. And then, the combined treatment would regulate the proportion of CD8+T cells to increase the PFS for digestive tract malignancy patients. Finally, Flow cytometry was used to validate the change of percentage for TAM and TIL. Our finding suggests the combined treatment of cordycepin and anti-CD47 mAb could significantly increase tumor suppression, which could increase M1-macrophage and decrease M2-macrophage. The PFS for digestive tract malignancy patients would be increased though regulation of CD8+T cells.